ANALYSIS OF MEDICAL ACTION CODING BASED ON ICD-9CM IN PARIAMAN REGIONAL GENERAL HOSPITAL (RSUD) - Rizqa Ramadhani; Yanti Desnita Tasri (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2021)
The use of the ICD-9 CM in coding medical actions will make it easier for us to classify patient action codes and facilitate reporting and facilitate BPJS claims in the JKN era which are useful as supporting administration, management and health research. This research was conducted at the Pariaman Regional General Hospital located Jalan Prof. Yamin SH No. 5, Kp. Baru, Pariaman Tengah, Kota Pariaman, West Sumatra on April 1 to April 14 2019. This study aims to determine the highest medical treatment based on ICD-9 CM at Pariaman Regional Hospital in 2019. This study uses a retrospective descriptive method with a quantitative approach. The research design used in this study was a descriptive cross-sectional study. The population used by all patient medical record files from April 1 to April 14 2019 was 303 medical record files. From the results of this study, it is known that there are 4 highest medical actions, namely SC action of 3 patients with code 74.99, Cataract aspiration action of 3 patients with code 13.41, VE action of 2 patients with code 72.7 and Thyroidectomy action of 2 patients with code 06.39.